BIOTECHNOLOGY IN AGRIBUSINESS FOR SOIL PREPARATION - Damasceno, Samara dos Santos; Rodolpho, Daniela (Revista Interface Tecnológica, 2024)
This article examines the role of biotechnology in soil preparation, highlighting its role in promoting more sustainable and efficacious agricultural practices. The research is based on a case study and a comprehensive review of the scientific literature. It examines the effectiveness of microorganisms such as Rhizobium, Azospirillum, Bacillus, and Pseudomonas, which act as biofertilizers. The study emphasizes the importance of biological nitrogen fixation, phosphorus solubilization, and plant growth hormone production, as well as the use of cover crops. The findings indicate that biotechnology has the potential to enhance soil health, enhance nutrient availability, and enhance soil structure, thereby enhancing crop productivity. The article concludes that investing in biotechnological innovations is a promising approach to address future agricultural challenges, while also aligning with present environmental and social demands. The implementation of sustainable practices in agribusiness necessitates the training of producers and assistance from government policies.
Keywords: biofertilizers.; microrganisms.; sustainability.